Franz Bach. Architekt und Unternehmer - Krause, Carmen (Mäzene für Wissenschaft, 2010)
With the 100th anniversary of Mönckebergstraße in the Free and Hanseatic City of Hamburg, the public was reminded in 2009 of who built the large office buildings in this remarkable shopping street. Franz Bach had a decisive influence on their architecture. Bach also worked as a master builder in various other places in the city. This biography, is the first one about Franz Bach. It traces the extraordinary life of this man: his talent, his architecture and his entrepreneurial spirit are highlighted as well as his social and cultural commitment as a citizen of Hamburg, who built a memorial to Heinrich Heine and Gottfried Semper and was one of the donors of the Hamburgische Wissenschaftliche Stiftung in 1907. Franz Bach's life story is at the same time an exciting journey through Hamburg's architectural history in the Wilhelmine Empire.